The wear resistance research of the rail contact surface depending on the grinding process - Protsenko, Pavlo; Borodii, Yurii; Bobyr, Mykola; Uhlmann, Eckart; Thalau, Janis; Lypovka, Pavlo (Mechanics and Advanced Technologies, 2019)
Background. Continuous mechanical loads on the rails during its contact with the wheel lead to an accumulation of residual stresses in the surface layers of the rails, resulting in fast-growing fatigue cracks. In addition, the interaction of the wheel and the rail leads to micro-and macro-slip during their contact, abrasive wear, as well as plastic deformation of the rail. Rail grinding is the repair method by which defective material layers removes from the rail surface, provides the necessary accuracy of size and shape as well as surface quality. Objective. The aim of the work is to determine the effect of grinding on the tribological properties of the rail surface and establish the optimal parameters of the grinding process to ensure the best wear resistance of the rail surface. Methods. The research on wear and contact damage of samples of surfaces cut from grinding rails conducted on a friction machine M-22M. The studies were carried out by dry friction of a sample (cut from a rail) with a counter-sample from the material used in the manufacture of railway wheels, for 1 hour, the friction path was 3.60 km. Samples were weighed on a VLR-200 balance before and after the study was performed on the friction machine. As a result, the mass wear value was determined for each sample. Results. Based on the results of tribological studies, we obtained graphical dependencies of the wear intensity on the hardness of surfaces of samples and histograms which showing the effect of grinding process parameters on the amount of the wear intensity of samples. In the work was investigated influence the next main parameters of the grinding process on wear resistance there are the temperature of the rail, depth of cut, grinding wheel speed. The results of the work can find practical application in railway transport when repairing rails by grinding. Conclusions. Based on the analysis of experimental data, the empirical relationship revealed between the depth of cut, the surface hardness of the sample and the intensity of its wear. The nature of the influence of grinding process parameters (rail temperature, depth of cut, grinding wheel speed) on the wear resistance of the rail surface is established. The most optimal values of the process parameters that provide greater wear resistance of the rail surface are depth of cut - 0.007 mm, grinding wheel speed - 30 m/s, rail temperature - 20°C (it is better to conduct the processing of rails in the warm season). The results of the work can find practical application in railway transport when repairing rails by grinding.